Preparation method of diatomic catalyst based on lignocellulose and application of diatomic catalyst in electro-catalytic reaction

Through a diatomic catalyst based on lignocellulose, the problem of insufficient activity of existing catalysts in the electrochemical reduction and ring opening reaction of 5-hydroxymethylfurfural is solved, and efficient and stable preparation of 2,5-hexanediol is achieved, with High selectivity and generation rate, suitable for commercial applications.

CN119506964AActive Publication Date: 2025-02-25UNIV OF SCI & TECH OF CHINA
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411803937.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-02-25
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

The existing catalysts cannot achieve efficient electrochemical activity in the electrochemical reduction ring-opening reaction of 5-hydroxymethylfurfural, resulting in the inability to effectively prepare high value-added 2,5-hexanediol.

Method used

Using a diatomic catalyst based on lignocellulose, the lignocellulose is modified by ammonium chloride, and through freeze-drying, programmed annealing and metal ion coordination, atomically dispersed diatomic catalyst is obtained to improve reactants and intermediates. Adsorption of the catalyst surface, thereby improving the activity and stability of the electrocatalytic reaction.

Benefits of technology

Achieved efficient electrocatalytic reduction and ring opening of 5-hydroxymethylfurfural, the selectivity of the product 2,5-hexanediol exceeds 90%, the generation rate reaches 190 μmol mgcat-1 h-1, and the reaction system is at room temperature and pressure It operates stably and has commercial application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506964A_ABST
    Figure CN119506964A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a lignocellulose-based diatomic catalyst and application of the lignocellulose-based diatomic catalyst in electro-catalytic reaction. Ammonium chloride is used as a nitrogen source to modify lignocellulose, the atom-dispersed Cu1Zn1 diatomic catalyst can be obtained through freeze drying, programmed annealing treatment and Cu < 2 + > and Zn < 2 + > coordination, the atom-dispersed Cu1Zn1 diatomic catalyst shows excellent activity and stability in an electro-catalysis biomass molecule upgrading reaction system, and 5-hydroxymethylfurfural can be converted into 2, 3, 4, 5-trimethyl-1, 3, 5-trimethyl-1, 3, 5-trimethyl-1, 3, 5-trimethyl-1, 3, 5-trimethyl-1, 3, 5-trimethyl-1, 3, 5- the selectivity exceeds 90%, and the yield exceeds 190 [mu] mol mgcat <-1 > h <-1 >. Technical economy analysis results show that the reaction system for preparing high-added-value chemicals through electrochemical reduction ring opening has commercial application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of inorganic material synthesis and electrocatalysis, and specifically relates to a preparation method of a diatomic catalyst based on lignocellulose and an application of the catalyst in an electrocatalytic reaction. Background Art

[0002] Compared with traditional nanocatalysts, the advantages of atomically dispersed catalytic materials mainly include three aspects: (1) fully exposed active metal atoms can achieve the maximum atomic utilization efficiency, reducing the cost of catalytic materials, especially precious metal catalytic materials; (2) by changing the coordination environment of the metal active site, the electronic and spatial structure of the metal can be effectively adjusted, thereby regulating its catalytic activity, selectivity and stability; (3) the precisely designed catalytic center structure is conducive to the establishment of computational models, providing a good platform for the study of the catalytic mechanism of the target reaction with the assistance of theoretical calculations. Based on the above advantages, atomically dispersed catalysts are widely used in various types of catalytic reaction systems.

[0003] In recent years, with the rapid growth of the world economy, the development of the chemical and energy industries has become increasingly dependent on the exploration and exploitation of oil, which has not only accelerated the depletion of fossil resources on the earth, but also caused serious environmental pollution. Using renewable biomass as raw materials to produce high-value-added chemicals can effectively alleviate human society's dependence on fossil resources and reduce environmental pollution. Biomass 5-hydroxymethylfurfural (HMF), as a carbon-neutral resource with abundant reserves, renewable and highly processable on the earth, is considered to be one of the most ideal alternatives for the sustainable production of biofuels / bioderived chemicals. Using electricity converted from renewable energy as the driving force, 5-hydroxymethylfurfural is converted into a variety of high-value-added chemicals and intermediates under mild conditions, which is a green way to achieve HMF conversion. 2,5-Hexanediol is an important high-value-added fine chemical that can be prepared by the electrochemical reduction ring-opening pathway of 5-hydroxymethylfurfural. However, the previously reported catalysts cannot achieve efficient electrochemical activity. Therefore, designing efficient and stable diatomic catalysts for the electrochemical reduction ring-opening reaction to prepare 2,5-hexanediol is of great significance for the realization of biomass molecular upgrading. Summary of the invention

[0004] The present invention is based on the electrocatalyst design concept and provides a method for preparing a diatomic catalyst based on lignocellulose and its application in electrocatalytic reactions. The present invention uses lignocellulose as a substrate to prepare a diatomic catalyst, and improves the adsorption of reactants and intermediates on the catalyst surface, thereby effectively improving the activity and stability of the electrocatalytic reduction ring opening of 5-hydroxymethylfurfural.

[0005] The present invention discloses a method for preparing a diatomic catalyst based on lignocellulose, wherein ammonium chloride is used as a nitrogen source to modify lignocellulose, and an atomically dispersed diatomic catalyst is obtained by freeze drying, programmed annealing treatment and metal ion coordination. Specifically, the method comprises the following steps:

[0006] Step 1: Mix lignocellulose nanocrystals with 0.1 M ammonium chloride solution and stir for 10-12 hours, followed by freeze drying and programmed temperature treatment to obtain nitrogen-doped lignocellulose.

[0007] Step 2: Take 100 mg of nitrogen-doped cellulose and mix it with a metal salt solution. The metal ions are adsorbed onto the surface of the nitrogen-doped cellulose through coordination. After high-temperature annealing in a protective atmosphere, a cellulose-based diatomic catalyst can be obtained.

[0008] In step 1, the lignocellulose nanocrystals are prepared by the following method:

[0009] Pulp board is used as raw material, crushed by a pulverizer, added with 64 wt% sulfuric acid solution for hydrolysis at 50°C for 6 hours, and then dialyzed with distilled water for 5-7 days to obtain wood cellulose nanocrystals.

[0010] In step 1, the programmed temperature rise process is set as follows: heating to 520° C. at a heating rate of 2° C. / min and keeping warm for 1 hour under an argon atmosphere, and then heating to 800° C. at a heating rate of 5° C. / min and keeping warm for 1 hour.

[0011] In step 1, the nitrogen content of the nitrogen-doped lignocellulose is 4.5-5.5 wt%.

[0012] In one embodiment, the nitrogen content of the obtained nitrogen-doped lignocellulose is 5.1 wt %.

[0013] In step 2, the metal salts are copper nitrate and zinc nitrate. The concentration of the metal salt solution is 10 mg / mL.

[0014] In step 2, the protective atmosphere is argon. The high temperature annealing treatment is to heat the solid obtained after centrifugation to 750°C at a heating rate of 5°C / min in an argon atmosphere and keep it warm for 2 hours; then the obtained product is pickled with hydrochloric acid and calcined again, specifically, heated to 900°C at a heating rate of 5°C / min in an argon atmosphere and kept warm for 2 hours.

[0015] In step 2, the content of metal atoms in the lignocellulose-based diatomic catalyst is 0.6-0.9wt%.

[0016] In one embodiment, the obtained lignocellulose-based copper-zinc diatomic catalyst has a copper content of 0.68 wt % and a zinc content of 0.72 wt %.

[0017] In the present invention, the metal sites are anchored on the surface of the lignocellulose-based carbon material through N coordination, showing the characteristics of an atomically dispersed catalyst.

[0018] The present invention discloses an application of a diatomic catalyst based on lignocellulose in an electrocatalytic hydrogenation reaction.

[0019] Specifically, the lignocellulose-based copper-zinc diatomic catalyst of the present invention is mixed with a nafion solution and uniformly coated on carbon paper with a loading of 1 mg / cm 2 , the working electrode of the electrocatalytic reaction can be obtained. The effective area of ​​the working electrode is 1cm 2 With the working electrode as cathode, the glassy carbon electrode as anode, and the Hg / HgO electrode as reference electrode, 5-hydroxymethylfurfural is dissolved in an alkaline electrolyte solution to form an electrolytic reaction device, so as to realize the electrocatalytic hydrogenation reduction of 5-hydroxymethylfurfural to prepare 2,5-hexanediol.

[0020] The changes of reactants and products were analyzed by hydrogen nuclear magnetic resonance spectroscopy.

[0021] The intermediates in the reaction process are detected through an in-situ reaction device to determine the reaction path.

[0022] The present invention uses an H-type electrolytic cell as a reaction device, including a working electrode, a reference electrode, a counter electrode, an electrolyte and a proton transport membrane. By comparing the reaction activity of the catalyst in an alkaline electrolyte and the electrochemical activity after adding HMF, the potential applied for the reaction is determined to be -0.4 V vs. RHE; by comparing the reaction activities of different types of catalysts, the structure of the catalyst is optimized; and by detecting the reactants and products, the optimal reaction conditions are determined.

[0023] Please follow the steps below:

[0024] (1) An H-type electrolytic cell was used as the reaction apparatus. 50 mL of electrolyte (1.0 M KOH solution) was added to the cathode and anode respectively. Argon was introduced into the electrolytic cell before the reaction to remove the oxygen dissolved in the electrolyte.

[0025] (2) A carbon rod was used as the working electrode at the anode, the prepared diatomic catalyst was used as the working electrode at the cathode, Hg / HgO was used as the reference electrode, and the reaction conditions were normal temperature and pressure. A linear voltammetric test was performed with a potential range of -1.5 to -0.8 V vs. Hg / HgO and a scan rate of 10 mV / s.

[0026] (3) Add HMF to the cathode electrolyte solution and stir to make it evenly dispersed. Then continue the linear voltammetry test with a potential range of -1.5 V to -0.8 V and a scan rate of 10 mV / s. By comparing with the linear voltammetry curve in (2), optimize the reaction potential. By comparing the linear voltammetry curves of different types of working electrodes, determine the catalyst with the best performance.

[0027] (4) Perform constant potential electrolysis within the reaction potential range. Take 100 μL of electrolyte, mix it with 100 μL of internal standard solution, then add 500 μL of heavy water. After mixing evenly, perform nuclear magnetic resonance hydrogen spectrum test to determine the content of reactants and products in the electrolyte, and then determine the optimal reaction conditions.

[0028] (5) Stability performance tests were performed under the optimal reaction conditions. The product yield and Faraday efficiency were detected in 50 cyclic electrolysis experiments. The working electrode after the cyclic experiments was physically characterized to determine the structural stability of the catalyst and the long-term cycle stability of the reaction system.

[0029] The present invention uses low-value-added 5-hydroxymethylfurfural as a reactant and dissolves it in an alkaline electrolyte solution, applies a potential of -0.4V vs. RHE for constant potential electrolysis, and detects the changes in reactants and products by nuclear magnetic resonance hydrogen spectrum. The product is mainly 2,5-hexanediol, with a selectivity of more than 90% and a yield of 190 μmol mg cat -1 h -1 , able to maintain stable electrolysis for 50 cycles.

[0030] The beneficial technical effects of the present invention are embodied in the following aspects:

[0031] 1. Compared with traditional thermochemical technology, the electrocatalytic reduction ring-opening reaction system provided by the present invention uses electric energy converted from renewable energy as the driving force, water as the proton source, and a diatomic catalyst derived from renewable biomass as the working electrode under the reaction conditions of normal temperature and pressure to achieve electrochemical reduction ring-opening of low-value-added biomass-derived molecules to prepare high-value-added chemicals.

[0032] 2. The electrocatalytic reduction ring-opening reaction system constructed by the present invention can convert HMF into high-value-added 2,5-hexanediol, the selectivity of the reaction product can exceed 90%, and the generation rate can reach 190 μmol mg cat -1 h -1 , far exceeding previously reported thermochemical and electrochemical conversion systems.

[0033] 3. The electrocatalytic reduction ring-opening reaction system constructed by the present invention has been found to have certain commercial application prospects through technical and economic analysis and performance comparison, and is in line with the strategic needs of the country's green development. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 is a transmission electron microscope image of the wood cellulose prepared in Example 1 of the present invention. Figure 1 It can be seen that wood cellulose presents the electron microscope structure of nanofibers.

[0035] Figure 2 is an atomic force microscope image of the wood cellulose prepared in Example 1 of the present invention. Figure 2 It can be seen that the surface structure of lignocellulose is relatively uniform.

[0036] Figure 3 is a transmission electron microscope image of N-doped wood cellulose prepared in Example 1 of the present invention. Figure 3 It can be seen that the electron microscopy structure of lignin did not change significantly after N doping.

[0037] Figure 4 is an atomic force microscope image of N-doped wood cellulose prepared in Example 1 of the present invention. Figure 4 It can be seen that the surface structure of lignin is still relatively uniform after N doping, without obvious changes.

[0038] Figure 5 1 is a comparison of the X-ray photoelectron spectra of N-doped lignocellulose and lignocellulose prepared in Example 1 of the present invention. Figure a is the XPS total spectrum of N-doped lignocellulose and lignocellulose, Figure b is the high-resolution XPS C 1s spectrum of N-doped lignocellulose and lignocellulose, Figure c is the high-resolution XPS O 1s spectrum of N-doped lignocellulose and lignocellulose, and Figure d is the high-resolution XPS N 1s spectrum of N-doped lignocellulose and lignocellulose. Figure 5 It can be seen that N was successfully introduced into lignocellulose by N doping.

[0039] Figure 6 The X-ray diffraction patterns of the CuZn diatomic catalyst and the corresponding single-atom catalyst prepared in Example 1 of the present invention are shown in FIG. Figure 6 It can be seen that the CuZn diatomic catalyst and the corresponding single atom catalyst only show graphitic carbon peaks.

[0040] Figure 7The specific surface area and pore size distribution of the CuZn diatomic catalyst and the corresponding single atom catalyst prepared in Example 1 of the present invention. Figure a is a specific surface area diagram of the CuZn diatomic catalyst and the corresponding single atom catalyst, and Figure b is a pore size distribution diagram of the CuZn diatomic catalyst and the corresponding single atom catalyst. Figure 7 It can be seen that there is no obvious difference in the specific surface area and pore size distribution between the CuZn diatomic catalyst and the corresponding single atom catalyst.

[0041] Figure 8 This is an atomically resolved high-angle annular dark field scanning transmission electron microscopy image of the CuZn diatomic catalyst prepared in Example 1 of the present invention. Figure 8 It can be seen that the CuZn diatomic catalyst exhibits the state of CuZn atomic pair distribution.

[0042] Fig. 9 : is the element distribution diagram of the CuZn diatomic catalyst prepared in Example 1 of the present invention. Fig. 9 It can be seen that Cu, Zn, C, and N elements are evenly distributed in the CuZn diatomic catalyst nanofibers.

[0043] Fig.10 : is the X-ray absorption near-edge structure diagram of the CuZn diatomic catalyst prepared in Example 1 of the present invention, wherein a and b are the X-ray absorption near-edge structures of Cu and Zn, respectively. Fig.10 It can be seen that the valence states of Cu and Zn in the CuZn diatomic catalyst are both close to +2.

[0044] Fig.11 1 is the Fourier transform X-ray absorption fine structure spectrum of the CuZn diatomic catalyst prepared in Example 1 of the present invention, wherein a and b are the X-ray absorption fine structure spectra of Cu and Zn, respectively. Fig.11 It can be seen that in the CuZn diatomic catalyst, both Cu and Zn exist in an atomically dispersed structure through N coordination.

[0045] Fig.12 : is the electrochemical reduction linear voltammetric curve of the CuZn diatomic catalyst prepared in Example 1 of the present invention. Fig.12 It can be seen that HMF can undergo electrochemical reduction reaction under the action of CuZn diatomic and Zn single atom catalysts.

[0046] Fig.13 1 is a comparison chart of the electrochemical reduction ring-opening reaction performance of the CuZn diatomic catalyst prepared in Example 1 of the present invention and the corresponding single-atom catalyst, wherein a and b are respectively the Faraday efficiency and product generation efficiency of the electrochemical reduction ring-opening of HMF to generate 2,5-hexanediol. Fig.13It can be seen that the CuZn diatomic catalyst has better reaction performance for the electrocatalytic reduction and ring-opening of HMF to prepare 2,5-hexanediol.

[0047] Fig.14 The performance of the CuZn diatomic catalyst prepared in Example 1 of the present invention is compared with that of other reaction systems. Fig.14 It can be seen that the reaction performance of CuZn diatomic catalyst for electrocatalytic HMF reduction and ring-opening to prepare 2,5-hexanediol is better than all the reported thermal catalytic and electrocatalytic reaction systems.

[0048] Fig.15 This is a technical and economic analysis diagram of the CuZn diatomic catalyst prepared in Example 1 of the present invention in this electrochemical reduction ring-opening reaction system. Fig.15 It can be seen that the reaction system of CuZn diatomic catalyst electrocatalyzing HMF reduction and ring-opening to prepare 2,5-hexanediol has commercial application prospects.

[0049] Fig.16 The nuclear magnetic resonance spectrum of the product of 2,5-hexanediol prepared by electrocatalytic reduction and ring-opening of HMF using the CuZn diatomic catalyst prepared in Example 1 of the present invention. Figures a, b, and c are the nuclear magnetic resonance spectra of HMF and the product, the standard fitting curve of HMF, and the standard fitting curve of the product, respectively. Fig.16 It can be seen that the conversion rate of HMF and the yield of 2,5-hexanediol can be accurately detected by nuclear magnetic resonance spectroscopy. DETAILED DESCRIPTION

[0050] The embodiment of the present invention provides a lignocellulose-based diatomic catalyst and a preparation method thereof, and by improving the adsorption of reactants and intermediates on the catalyst surface, the activity and stability of the electrocatalytic reduction ring opening of 5-hydroxymethylfurfural on the diatomic catalyst surface are effectively improved.

[0051] The present invention is further described in detail below through specific examples.

[0052] Example:

[0053] In this example, a lignocellulose-based diatomic catalyst was first prepared and used as the working electrode material to further assemble the HMF electrochemical reduction ring-opening reaction system. The specific operation steps are as follows:

[0054] 1. Disperse 100 mg of lignocellulose in 50 mL of ammonium chloride aqueous solution (concentration of 0.1 mol / L) and stir thoroughly at room temperature for 10 hours. The solid product was obtained by centrifugal separation, freeze-dried at -78°C for 48 hours, and then programmed to heat up to 520°C at a heating rate of 2°C / min in an argon atmosphere and keep warm for 1 hour, and then heated to 800°C at a heating rate of 5°C / min and kept warm for 1 hour to obtain N-doped lignocellulose. The transmission electron microscopy of the obtained N-doped lignocellulose is as follows Figure 3 As shown, atomic force microscopy Figure 4 As shown, the X-ray photoelectron spectrum is as follows Figure 5 shown.

[0055] 2. Disperse 50 mg of N-doped cellulose in 30 mL of ethanol solution, then add 2 mL of freshly prepared copper nitrate solution (10 mg / mL) and 2 mL of freshly prepared zinc nitrate solution (10 mg / mL) to the above ethanol solution and stir for 12 hours. The black solid was obtained by centrifugation, and heated to 750°C at a heating rate of 5°C / min in an argon atmosphere and kept warm for 2 hours. The obtained black product was washed with hydrochloric acid and calcined again at high temperature, and heated to 900°C at a heating rate of 5°C / min in an argon atmosphere and kept warm for 2 hours to obtain a cellulose-based CuZn diatomic catalyst. The X-ray diffraction pattern of the obtained cellulose-based CuZn diatomic catalyst is shown as follows Figure 6 As shown, the specific surface area and pore size distribution are Figure 7 As shown, the atomically resolved high-angle annular dark-field scanning transmission electron microscopy image is shown in Figure 8 The element distribution is shown in Fig. 9 shown.

[0056] 3. The above-mentioned lignocellulose-based CuZn diatomic catalyst was mixed with lithium fluoride and subjected to synchrotron radiation testing. The X-ray absorption near-edge structure of the obtained CuZn diatomic catalyst is as follows: Fig.10 The Fourier transformed X-ray absorption fine structure spectrum of the CuZn diatomic catalyst is shown in Fig.11 shown.

[0057] 4. Disperse 5 mg of catalyst in 1 mL of ethanol solution and add 100 μL of Nafion solution. Then take 200 μL of the mixed solution and evenly distribute it on carbon paper (1×1 cm 2 ), and then dried to obtain a working electrode. The corresponding single-atom catalyst is also loaded on carbon paper in the same way to obtain the corresponding working electrode.

[0058] 5. Use a proton exchange membrane to separate the H-type electrolytic cell, use 1.0 M KOH as the electrolyte, the electrode prepared above as the working electrode, the Hg / HgO electrode as the reference electrode, and the carbon rod as the counter electrode. Perform a linear voltammetric curve with a scan rate of 5 mV / s, no impedance compensation, and a potential range of -0.5 to 0.1 V vs. RHE. Without adding HMF, a linear voltammetric test was performed, and then HMF was added to the working electrode side. It was found that when the applied potential was lower than -0.2 V vs. RHE, an obvious reduction current appeared, indicating that HMF reduction occurred at this time, and the CuZn catalyst's response to the current was significantly stronger than that of the Zn catalyst. The corresponding linear voltammetric curve is shown in the figure below. Fig.12 shown.

[0059] 6. Potentiostatic electrolysis was performed at -0.15, -0.20, -0.25, -0.30, -0.35, -0.40, -0.45, -0.50 V vs. RHE potential, and the distribution of the products was detected by nuclear magnetic resonance spectroscopy. By comparing the Faraday efficiency and product formation rate of HMF reduction ring opening to 2,5-hexanediol, it can be found that the CuZn diatomic catalyst exhibits the best electrochemical reduction ring opening activity. The corresponding electrochemical reduction ring opening performance is compared as follows Fig.13 shown.

[0060] 7. Comparing the reaction performance of HMF reduction ring opening in this reaction system with relevant literature, it can be found that this reaction system has the best electrochemical performance and stability. Through technical and economic analysis, it can be found that this reaction system has commercial application prospects. The corresponding performance comparison is as follows Fig.14 The corresponding technical and economic analysis diagram is shown in Fig.15 shown.

[0061] It will be easily understood by those skilled in the art that the above embodiments are merely preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a diatomic catalyst based on lignocellulose, characterized in that: Ammonium chloride is used as a nitrogen source to modify lignocellulose, and an atomically dispersed diatomic catalyst is obtained by freeze drying, programmed annealing and metal ion coordination; the steps include: Step 1: Mix lignocellulose nanocrystals with 0.1 M ammonium chloride solution, stir for 10-12 hours, and then freeze-dry and program temperature to obtain nitrogen-doped lignocellulose; Step 2: The nitrogen-doped cellulose prepared in step 1 is mixed with a metal salt solution, and metal ions are adsorbed onto the surface of the nitrogen-doped cellulose through coordination, followed by high-temperature annealing in a protective atmosphere to obtain a cellulose-based diatomic catalyst.

2. The preparation method according to claim 1, characterized in that: In step 1, the lignocellulose nanocrystals are prepared by the following method: Pulp board is used as raw material, crushed by a pulverizer, added with 64 wt% sulfuric acid solution and hydrolyzed at 50°C for 6 hours, and then dialyzed with distilled water for 5-7 days to obtain wood cellulose nanocrystals.

3. The preparation method according to claim 1, characterized in that: In step 1, the programmed temperature rise process is set as follows: heating to 520° C. at a heating rate of 2° C. / min and keeping warm for 1 hour under an argon atmosphere, and then heating to 800° C. at a heating rate of 5° C. / min and keeping warm for 1 hour.

4. The preparation method according to claim 1, characterized in that: In step 1, the nitrogen content of the nitrogen-doped lignocellulose is 4.5-5.5 wt%.

5. The preparation method according to claim 1, characterized in that: In step 2, the metal salts are copper nitrate and zinc nitrate.

6. The preparation method according to claim 1, characterized in that: In step 2, the protective atmosphere is argon.

7. The preparation method according to claim 6, characterized in that: The high temperature annealing treatment is to heat the solid obtained after centrifugation to 750°C at a heating rate of 5°C / min in an argon atmosphere and keep it warm for 2 hours; then the obtained product is pickled with hydrochloric acid and calcined again, specifically, heated to 900°C at a heating rate of 5°C / min in an argon atmosphere and kept warm for 2 hours.

8. The preparation method according to claim 1, characterized in that: In step 2, the content of metal atoms in the lignocellulose-based diatomic catalyst is 0.6-0.9 wt %.

9. Use of the diatomic catalyst based on lignocellulose prepared by the preparation method according to any one of claims 1 to 8 in an electrocatalytic hydrogenation reaction.

10. The use according to claim 9, characterized in that: The cellulose-based diatomic catalyst is mixed with a nafion solution and uniformly coated on carbon paper to obtain a working electrode for an electrocatalytic reaction; the working electrode is used as a cathode, a glassy carbon electrode is used as an anode, and a Hg / HgO electrode is used as a reference electrode, 5-hydroxymethylfurfural is dissolved in an alkaline electrolyte solution to form an electrolytic reaction device, and the electrocatalytic hydrogenation reduction of 5-hydroxymethylfurfural is achieved to prepare 2,5-hexanediol.

Citation Information

Patent Citations

  • Preparation method of nanocrystal cellulose

    CN106676927A

  • Preparation method of high-efficiency and low-cost oxygen reduction catalyst

    CN108199053A

  • Nitrogen-doped porous carbon-supported bimetallic catalyst and preparation method and application thereof

    CN109999880A

  • Preparation method of nitrogen-doped carbon-based ruthenium-loaded catalyst for hydrogen evolution by electrolysis

    CN113684502A

  • Transition metal-loaded carbon fiber catalyst and preparation and application thereof in electro-catalytic synthesis of hydrogen peroxide

    CN114703504A